Behavioural Responses of Trichogramma Papilionis Nagarkatti, Egg Parasitoid of Maize Borer, Ostrinia Furnacalis (Guen.) to Semiochemicals from Maize Plant and Selected Weeds - Ulpah, Saripah (2006)
Manipulation of parasitoid behaviour for the purposes of habitat location and host finding could optimise the utilisation of biological control agents in pest management. In order to be able to do so, factors that elicit such behavioural responses of the parasitoid need to be elucidated. As such, members of the first trophic level, i.e maize and associated weeds, were investigated for possible semiochemicals by determining their attractancy, arrestant and activation effects of the plant chemicals to the third trophic level, i.e. Trichogramma papilionis Nagarkatti, the egg parasitoid of the Asiatic maize-borer, Ostriniafirnacalis (Guen.). Attractancy effects of volatile plant chemicals of selected weeds and extracts of maize leaf of various growth stages were studied using a modified linear olfactometer. Contact effects of plant chemicals on the retention time of T. papilionis were investigated in a glass cylinder arena, and by tracing the locomotion of female parasitoid upon encountering plant chemical patch. Effects of plants chemicals on parasitization rate by T. papilionis were evaluated in Petri-dish and in cage experiment. Effects of stimulation from plant chemicals prior to parasitoid release was studied in the laboratory. A Field trial was conducted to probe the response of naturally occurring Trichogramma to the extracts of Amaranthus hybridus, a weed species found to elicit positive response in T. papilionis. The weeds studied were Ageratum conyzoides, Amaranthus hybridus, Asystasia gangetica, Borreria latifolia, Cleome rutidosperma, Cyperus rotundus and Eleusine indica. Results of experiments using linear olfactometer revealed that volatiles from fresh plant material of A. gangetica, C. rutidosperma and A. hybridus showed attractancy effects, on the contrary, that of A. conyzoides showed repellent effect, while those of B. latifolia, C. rotundus and E. indica did not elicit significant response to the parasitoid compared to control. Extracts of maize leaf at early-whorl stage did not cause significant difference in T. papilionis rate of displacement at concentrations 0.005 g/ml and 0.05 g/ml; extract of maize leaf from tasseling/silking stages, however, elicited significant responses at both concentrations tested. Through contact effect studies, extracts of early-whorl stage at all concentration tested (0.001, 0.01, and 0.03 g/ml), did not result in the increase of retention time by the female parasitoid. However, increasing the extract concentration of other maize stages generally increased the retention time of the parasitoid. Silking stage at 0.03 g/ml revealed highly significant difference. Surface extract of A. hybridus resulted in signrficantly higher retention time at all concentration tested (1,2 and 3 g/rnl). The extract from C. rutidospemza did not cause any significant difference at aU concentration tested, while that of A.gangetica gave significant difference only at the highest concentration. Extract of Ageratum, however, caused significantly reduced retention time. Female parasitoids that were allowed to oviposit prior to being used in the experiment showed extended retention time in Petri dish testing. Parasitization experiments revealed that the extracts of maize leaves and of two weeds, A. gangetica, and A. hybridus, significantly increased the parasitization of Corcyra cephalonica eggs by the T. papilionis. Pre-release stimulation using the extracts of maize and A. hybridus increased parasitization rates. In field trials inconclusive results were obtained due to the unusually low parasitoid number during the experiment. However, the performance of Trichogramrna in the field seemed to be enhanced with the application of A. hybridus extract. It is concluded that T. papilionis seemed to be adaptive to chemicals from maize, the host plant of its natural host, 0. jimacalis. The response, however, varied depending on plant stage of plant growth. Trichograrnrna papilionis showed positive responses to chemicals from A. hybridus which were comparable to those caused by maize leaves extracts. Since response of the parasitoid varied among weeds present in maize field ecosystem, selective weeding would be able to enhance the parasitoid performance. Amaranthus hybridus showed the prospect to be utilised for manipulation of the parasitoid foraging behaviour, for the purpose of the maize borer control, and the possibility of bridging the T. papilionis to other lepidopteran pest in other crop system. The methods, however, need further refinement.